Timing belt gearbox in Ballbot robot - Akbari, M.; Zabihi Kheibari, Hosein; Moosavi Nejad, Atefe Sadat (2013 First RSI/ISM International Conference on Robotics and Mechatronics (ICRoM), 2013)
Ballbot is one of the dynamically stable robots that is much more complex than statically stable robots. This robot is able to keep balance on the ball with very precise control mechanisms. Very accurate and smooth motion without motor backlash is important to stabilize this robot. If you use the gearbox motor, due to backlash in the gearbox gears, we will have errors in calculating the exact position of the wheels and also make robot oscillation on the ball that will cause robot instability. That's why in accurate applications, gearbox motors are used less. To solve the backlash problem, some methods have been proposed that generally require high technology and cost. In this paper, the proposed method for robot motion with high accuracy and low backlash, is using timing belt gearboxes for power transmission that requires no special technology and is less costly method, furthermore due to the weight and volume it has, creates a proper torque. By using this method to transfer power and precise control of motors, the robot has a good balance and quick reaction to the tensions.